2011
DOI: 10.5152/jtgga.2011.01
|View full text |Cite
|
Sign up to set email alerts
|

Are pregnancy complications increased in poor responders?

Abstract: Objective: To investigate whether pregnancy complications are increased in poor responders to ovarian stimulation in IVF treatment. Material and Methods:We reviewed the antenatal follow up and birth records of 26 poor responders to ovarian stimulation and 125 normoresponder patients in an IVF program.Results: Eighty nine (71.2%) of the normoresponders and 22 (84.6%) of the poor responders had no pregnancy complications. Gestational diabetes was present in 18 (14.4%) of the normoresponders and 3 (11.5%) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…There was no significant difference between the two groups in terms of hypertensive disorders of pregnancy (HDP), pre-eclampsia, and newborn birth weight. Huriye [ 11 ] defined POR patients as those whose retrieved oocytes were less than six and matched cases and controls based on age. He found that the risks of gestational diabetes mellitus (GDM) and fetal disorders in POR patients did not increase.…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference between the two groups in terms of hypertensive disorders of pregnancy (HDP), pre-eclampsia, and newborn birth weight. Huriye [ 11 ] defined POR patients as those whose retrieved oocytes were less than six and matched cases and controls based on age. He found that the risks of gestational diabetes mellitus (GDM) and fetal disorders in POR patients did not increase.…”
Section: Introductionmentioning
confidence: 99%